2017
DOI: 10.1007/s00704-017-2050-8
|View full text |Cite
|
Sign up to set email alerts
|

Joint atmospheric-terrestrial water balances for East Africa: a WRF-Hydro case study for the upper Tana River basin

Abstract: For an improved understanding of the hydrometeorological conditions of the Tana River basin of Kenya, East Africa, its joint atmospheric-terrestrial water balances are investigated. This is achieved through the application of the Weather Research and Forecasting (WRF) and the fully coupled WRF-Hydro modeling system over the MathioyaSagana subcatchment (3279 km 2 ) and its surroundings in the upper Tana River basin for 4 years (2011)(2012)(2013)(2014). The model setup consists of an outer domain at 25 km (East … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 41 publications
4
72
0
Order By: Relevance
“…In the future, a more in‐depth sensitivity analysis of the WRF‐Hydro model parameters could be beneficial. Nonetheless, the performance of WRF‐Hydro in this study is comparable to those previously reported in the literature (Givati et al, ; Kerandi et al, ; Naabil et al, ; Salas et al, ; Silver et al, ; Yucel et al, ).…”
Section: Resultssupporting
confidence: 90%
“…In the future, a more in‐depth sensitivity analysis of the WRF‐Hydro model parameters could be beneficial. Nonetheless, the performance of WRF‐Hydro in this study is comparable to those previously reported in the literature (Givati et al, ; Kerandi et al, ; Naabil et al, ; Salas et al, ; Silver et al, ; Yucel et al, ).…”
Section: Resultssupporting
confidence: 90%
“…Figure 15 illustrates the ensemble mean and range of the 14-day filtered terms of the differential atmospheric water budget (equation (7)) between WRF and WRF-Hydro ensembles. It shows that evapotranspiration differences between the WRF and WRF-Hydro simulations are small in comparison to the other terms of the budget and that precipitation differences are mainly related to differences in atmospheric water transport through the budget area, that is, I-O in equation (7), as, for example, in Kerandi et al (2018). This suggests that the precipitation differences between WRF and WRF-Hydro members in the budget area are mainly driven by internal model variability and that the increase of evapotranspiration amounts in WRF-Hydro has a minor contribution.…”
Section: 1029/2018jd029004mentioning
confidence: 95%
“…In order to analyze the atmospheric fluxes and the regional water cycle over the ENB, two additional bulk characteristics were used following References [25,[38][39][40]: precipitation efficiency (χ) and moisture recycling ratio (β).…”
Section: Atmospheric Water Balancementioning
confidence: 99%
“…Previous studies have investigated water balance using either atmospheric or terrestrial water storage. Kerandi et al [25] applied a fully coupled modeling system for the weather research and forecasting (WRF) and WRF-Hydro models over the upper Tana River Basin at Kenya. Two nesting domains were used for the WRF simulation, with spatial resolutions of 25 km and 5 km, respectively, while a 500 m routing resolution was used for the WRF-Hydro model.…”
Section: Introductionmentioning
confidence: 99%